How family communication can help to intervene mental health issues among youngsters / Muhammad Syafi Fauzan Saifuddin … [et al.] - Saifuddin, Muhammad Syafi Fauzan; Gonsilou, Isaac Ryan; Saiful Haizam, Syafiqa Humaira; Yari, Emilson Rudalf; Rosman, Nur Elya Maisara; Hassan, Mohd Sufiean (Faculty of Communication & Media Studies, 2024)
This paper aims to draw an analyst's review on how family communication can help intervene in mental health issues among youngsters by examining the relationship between family communication and mental health issues. By using the ATLAS.ti 23 approach, this study attempts to conduct a systematic overview of the mental health issues and family communication studies published in Scopus from 2019 to 2023. This study aims to determine the prevalent strategies for intervening in mental health issues among youngsters through the role of family communication. By using auto-coding links in ATLAS.ti 23 also may reveal youngsters' and families' communication relationships and mental health issues intervention measures. A thematic analysis of these 21 articles identified 13 initial codes characterizing youngsters and family communication relationships and mental health issues intervention through those two groups in terms of communication. The five most interesting discoveries that have been found in this concept are the linkages between parent-child communication, parental involvement, family communication pattern, attachment style, and a family-focused treatment. The parent-child communication term is the most used in the articles. This study shows how data analysis can be used to find the trend or direction that reflects characteristics important to youngsters in mental health issues intervention.